Epistemic citizenship: a new defense of role-based epistemic normativity - Kirchner, John J. S., author; Kasser, Jeff, advisor; Tropman, Elizabeth, committee member; MacDonald, Bradley, committee member (Colorado State University. Libraries, 2023)
One problem facing epistemic deontology is its (apparent) incompatibility with doxastic involuntarism. Intuitively, deontic epistemic evaluations—e.g., blame or reproach for unjustified belief—seem unbefitting if we can't control that which we believe. However, Richard Feldman proposes a solve to this seeming incompatibility, which is a role-based approach to epistemic normativity. When we find ourselves within certain roles, the normativity of performing within one's role appropriately, as one ought, can generate obligations, permissions, duties, etc. If we can rightly conceive of a "believer role," then we can have coherent deontological normativity, even if we, in fact, lack control over our doxastic attitudes. However, Matthew Chrisman advances strong criticisms of the role-based approach, criticisms which I will argue ultimately fail. In response to Chrisman, I will argue that our doxastic role as a believer is akin to our role as political citizens. The upshot of the project will be a revitalized defense of role-based epistemic deontology, and a more apt analogy, i.e., that of epistemic citizen. Chrisman's assertions of the role-based approach's inherent explanatory insufficiencies will be shown to be unfounded once role-normativity itself is understood more precisely.